Evaluating the thermal environment in a naturally ventilated high-rise residential college building / Nur Ain Syahirah Dalid, Fairus Muhamad Darus and Rabiatul Adawiyah Nasir - Dalid, Nur Ain Syahirah; Muhamad Darus, Fairus; Nasir, Rabiatul Adawiyah (College of Built Environment, 2023)
In students hostels, thermal comfort is important because it can impact students' comfort, health, learning, and overall quality of life.